Religion and the nation-state in South Korea: a case of changing interpretations of modernity in a global context - Koenig, Matthias (Social compass, 2000)
The author explores changing interpretations of modernity in a global context by analysing discourses and policies governing the relation of the nation-state and religion in post-Liberation South Korea. For a long time, the models of religion and of the nation-state that formed part of the occidental interpretation of modernity influenced discursive and political practices in South Korea. In the 1980s, however, these have become increasingly engaged in the self-reflexive construction of a non-occidental modernity, one that has allowed for a re-appraisal of Confucian traditions and for a revaluation of religions. It is argued that these shifts are embedded in more general changes of cognitive and normative frames as diffused in global discursive and institutional frameworks, thus successively depriving the West of its hegemonic position in interpreting the universalistic aspirations of modernity.